The Dynasty Politics of The Queen Atut Family and its Influence on Political Ethics In Regional Head Elections In Banten - Nabila Syamsa, NabilaSyamsa; Sunarso, Sunarso; Handayani, Wuri (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze the influence of the dynasty politics of Ratu Atut's family on political ethics in regional head elections in Banten Province. The growing dynasty politics in this region have strengthened the dominance of family power in various sectors, limited public participation, and hampered the regeneration of healthy leadership. The research method used is a qualitative literature study approach, where data were collected through participant observation and analysis of historical and contemporary documents. The results show that dynasty politics in Banten worsens political ethics by ignoring the principles of justice, equality, and transparency in regional head elections. The practices of nepotism and collusion that occur reduce the effectiveness of democracy and worsen the quality of governance. This study suggests the need for regulations that limit the practice of political dynasties so that regional head elections can be carried out based on the competence and integrity of prospective leaders, rather than on family relationships.